2017
DOI: 10.1002/biot.201700390
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and Accessible Automated Operation of Miniature Chromatography Columns on a Liquid Handling Station

Abstract: The High Throughput (HT) investigation of chromatographic separations is an important element of downstream bioprocess development due to the importance of chromatography as a technique for achieving stringent regulatory requirements on product purity. Various HT formats for chromatography exist, but the miniature column approach has characteristics resembling large scale packed bed column chromatography the most. The operation of such columns on robotic stations can be automated, but this is not always a stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…In the past, the integration of robotic systems for downstream process development led to significant increases in the throughput of several standard operation procedures. For example, cell lysis has been optimized for improved release of intracellular products, the screening of chromatographic material and binding/elution conditions was facilitated, and the identification of optimal compositions of aqueous two‐phase systems or precipitation conditions has become experimentally feasible. So far only a few but highly interesting studies have been reported that combine high‐throughput upstream and downstream bioprocess development .…”
Section: Microbioreactor (Mbr) Systemsmentioning
confidence: 99%
“…In the past, the integration of robotic systems for downstream process development led to significant increases in the throughput of several standard operation procedures. For example, cell lysis has been optimized for improved release of intracellular products, the screening of chromatographic material and binding/elution conditions was facilitated, and the identification of optimal compositions of aqueous two‐phase systems or precipitation conditions has become experimentally feasible. So far only a few but highly interesting studies have been reported that combine high‐throughput upstream and downstream bioprocess development .…”
Section: Microbioreactor (Mbr) Systemsmentioning
confidence: 99%
“…(a) Fermentations carried out at the indicated pH, (b) fermentations carried out with a pH pulse or pH shift, (c) scale for P2-VP8-P [4] concentration, the area of the circle showing full-length and truncated P2-VP8-P [4] species (a and b) is proportional to its concentration in the supernatant 2 or 20 μL per well (GE Healthcare Life Sciences) 27 or 0.6 mL RoboColumns (custom packed by Repligen Europe B.V, Breda, The Netherlands). 28 A total of 18 resins were screened for binding capacity and product quality (Table 1)…”
Section: Chromatography: Resin Selectionmentioning
confidence: 99%
“…While batch HT methods allow the evaluation of multiple conditions in parallel, including binding capacity measurements from small product masses due to the low volumes of stationary phases employed. Moreover, the miniature packed bed column technique (i.e., RoboColumns) can be easily scaled-up or -down [7]. It can also return an efficient way of evaluating different stationary phases due to the advantage of packing any beaded based resin at a cost.…”
Section: Introductionmentioning
confidence: 99%
“…The followed workflow employs a Tecan Freedom EVO® 200 automated liquid handling station (Tecan Group Ltd., Männedorf, Switzerland) and MATLAB® (The MathWorks, MA, USA) codes, compiled into executables, which convert user-defined inputs into robotic commands. These are then executed within generic Tecan Freedom EVOware® (Tecan Group Ltd.) based scripts that implement all necessary actions to complete a study with no end-user intervention [7]. Here, both 0.2 and 0.6 mL columns, packed with various types of resin, can be used in flowthrough or bind and elute mode, with the latter employing isocratic, multi-step and multi-slope gradient elution.…”
Section: Introductionmentioning
confidence: 99%